Postinjury employment as a surrogate for functional outcomes: a quality indicator for trauma systems - Parks, Jennifer K. (Baylor Health Care System, 2010)
Return to work may be easily monitored as a surrogate of long-term functional outcome for benchmarking and performance improvement of trauma systems. We hypothesized that employment rates among survivors of traumatic brain injury (TBI) decrease following injury and remain depressed for an extended period of time. Data were obtained from a statewide surveillance system of 3522 TBI patients (aged >15 years) who were discharged alive from acute care hospitals and followed yearly using telephone interviews (1996–1999). The study population consisted of patients with severe TBI (head abbreviated injury score 3, 4, or 5) and complete follow-up for 3 years postinjury (n = 572). Patients were mostly young males (43 ± 19 years, 65% male) with blunt TBI (92%). The preinjury employment rate was 67%, which declined to 52% (P < 0.001) in the first year and slowly rose in subsequent years but never reached the preinjury level (54% in year 2, P < 0.001; 57% in year 3, P = 0.001). Increasing severity of TBI was associated with a lower employment rate. Patients who remained employed worked the same number of hours as they did before the injury (47.8 ± 10.5 hours). Female employment rates rose similar to rates for males. However, women who were employed full-time before TBI were more likely to work part-time after TBI than men (50% vs 24%, P < 0.001). In conclusion, survivors of severe injury do not attain preinjury employment levels for several years. Once validated in other studies, postinjury employment may be used as an indicator to monitor functional outcomes in trauma registries.